Factors associated with vaccine adhesion and notions of knowledge of sarampo in habitant of the cities of Belém and Ananindeua, Pará, Brazil, 2016 to 2018 (Research, Society and Development, 2023)
Measles is a global public health problem, eliminated from Brazil in 2016 resurfacing as an outbreak in the year 2018 in several states, imported from Venezuela. In 2019 there was an upsurge of measles, both nationally and internationally, a consequence of low vaccination coverage, leading some countries to lose their elimination certification, including Brazil, with the state of Pará registering a high incidence of the disease in 2020. The objective of the study was to evaluate the knowledge of the population aged 15 to 39 years, about measles infection and its risks in the cities of Belém and Ananindeua, between 2016 and 2018. They were interviewed through questionnaires to collect information, digitized in Epi-Info™ v7.0 software database for analysis of the desired variables. This population demonstrated in both municipalities that measles is an immunopreventable disease, but ignorance by the means of transmission. The proportion of knowledge about the virus did not differ between genders, as well as between vaccinated and unvaccinated people, but the difference was significant between age groups and level of education. There is a need for clarification to the population through continued education, showing the public health problem caused by the lack of true knowledge.